Tubular Carbon Membrane Prepared from PI/NCC: Effects of Pyrolysis Atmosphere - Norazlianie, Sazali; Wan Norharyati, Wan Salleh; Ahmad Fauzi, Ismail; Nur Izwanne, Mahyon; K., Kadirgama; Mohd Shahrizan, Moslan (AIDIC Servizi, 2019)
The performance of Tubular Carbon Membrane (TCMs)due to pyrolysis conditions was studied. Dip-coating technique was used to synthesize the P84 co- polyimide/Nanocrystalline cellulose-based TCM, and pure gas O2 and N2 were used to determine the permeation properties of the TCMs. Different atmosphere i.e Argon, Nitrogen and Helium were introduced during the heat treatment processes at a flow rate of 200 mL/min to enhance the membrane’s performance. The pyrolysis temperature and heating rate were set at 800 °C and 3°C/min. It was found that the best pyrolysis condition for the preparation of PI/NCC-based TCMs was conducted in Argon atmosphere with the permeance of 3.22±3.21 and 29.90±2.98 GPU for N2, and O2 gas. The membrane also demonstrated that the highest O2/N2 selectivity of 9.29±2.54. In comparisons to all other carbonization atmosphere, preparation of TCMs in Ar atmosphere showed the lowest weight loss and revealed the highest N2 selectivity in this study.